Circular bioeconomy as a driver of regenerative multifunctional landscapes - Somorin, Tosin; Zemadim, Birhanu; Osei-Amponsah, Charity; Adamtey, Noah; Gebrezgabher, Solomie A. (International Water Management Institute, 2025)
This position paper advocates for a systematic integration of Circular Bioeconomy (CBE) principles into the design and implementation of Multifunctional Landscapes (MFLs) as a pathway to achieving low-carbon, resource efficient, socially inclusive, and ecologically balanced development. Combining these approaches can regenerate degraded agricultural landscapes, strengthen rural–urban linkages, and diversify rural economies, opportunities that remain largely underexploited in current practice. CBE provides practical strategies for closing nutrient, water, energy, and material loops, transforming organic waste and residues into valuable inputs such as biofertilizers, water, renewable energy, and bio-based materials. These approaches can reduce reliance on synthetic inputs, lower greenhouse-gas emissions, reduce freshwater use, and rebuild soil fertility, while generating new rural enterprises and livelihood opportunities that reinforce local value chains. MFLs, by contrast, seek to harmonize land uses to deliver multiple ecosystem services, such as biodiversity conservation, soil regeneration, water regulation, carbon storage, and livelihoods, through participatory planning and adaptive governance. When pursued jointly, both frameworks can transform rural territories into resilient socio-ecological systems that deliver economic value while maintaining ecological integrity. Yet, current efforts to integrate CBE into landscape initiatives are fragmented. For example, many existing landscape programs focus primarily on biophysical design, with limited consideration for the regenerative business models and economic systems needed to sustain multifunctionality over time. In these landscapes. mechanisms that support circular resource flows, value retention, and inclusive livelihood opportunities are often overlooked or insufficiently embedded in management strategies. Policy incoherence, particularly incentives favoring bioenergy over higher-value material uses, drives maladaptation and feedstock overexploitation. Market-driven biomass production risks degrading soils, water quality, and biodiversity. Governance is often siloed, with limited cross-sectoral coordination and weak participation of women, smallholders, and indigenous groups. More importantly, financial and investment mechanisms to reward circular practices are poorly developed, and data on resource and waste flows are scarce, outdated, or inconsistent, limiting evidence-based planning and investment. This paper calls for policy coherence, inclusive governance, innovative financing, and integrated knowledge systems to mainstream circularity in landscape management.